Direct effects of quercetin on impaired reactivity of spontaneously hypertensive rat aortae: comparative study with ascorbic acid - Ajay, M.; Achike, F.I.; Mustafa, A.M.; Mustafa, Mohd Rais (2006)
1. There is a growing interest in the anti-oxidant characteristics and use of ﬂavonoids in the management of cardiovascular diseases. The cardiovascular mechanism of action of these plant derivatives remains controversial. This study compared the effects of the ﬂavonoid quercetin with those of the anti-oxidant vitamin ascorbic acid (vitamin C) on the reactivity of aortic rings from spontaneously hypertensive rats (SHR).